SIMULASI KINERJA GOLD CODE PADA SISTEM KOMUNIKASI DIRECT SEQUENCE SPREAD SPECTRUM (DSSS) MELALUI KANAL MULTIPATH FADING - Zainul Halim, Muhamad; Pramaita, Nyoman; Sudiarta, Pande Ketut (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUM, 2021)
The communication channel cannot be separated from noise, interference and fading. To minimize mutual interference, you can use a scatter code. This research uses Gold Code with a code length of 31. This simulation aims to determine the effect of the number of multipath components on the Gold Code performance of multipath fading channels. This simulation uses digital modulation, namely BPSK (Binary Phase Shift Keying). In the simulation of flat fading channel with 1 multipath component number, the results of the comparison of simulated BER with theoretical BER are almost the same so that the simulation results can be said to be valid and can be used on selective fading channels. In the simulation of frequency selective fading channels with variations of multipath components have different values, this happens due to interference. In this simulation, the number of multipath 27 components that have the most disruptive signals results in the worst performance. In multi-user cross-correlation, it has poor performance, seen from the cross-correlation function, where the correlation value of user 1 with 2, 3 and 4 is more than 0, this value indicates the user is being interfered with by other users.